Guided Inquiry Method and Self-Efficacy on High School Students' Physics Learning Outcomes - Riben, Sulfa; Arsyad, Muhammad; Helmi, Helmi (LPPM Undiksha, 2024)
A change in the learning paradigm is needed to develop a scientific attitude to form students who are creative, critical, open, innovative, and competitive. This study aims to analyze the effect of the guided inquiry learning method and self-efficacy on students' physics learning outcomes. This research is true experimental research that compares the application of the guided and free inquiry methods. This study involved 70 students from 2 classes selected by simple random sampling. The instruments used in this study were self-efficacy questionnaires and student learning outcomes. The data collected were then analyzed descriptively and inferentially using SPSS 20. The results showed that applying the inquiry method and self-efficacy influenced students' physics learning outcomes. Applying the guided inquiry method and high student self-efficacy resulted in high learning outcomes. Conversely, they applied the free inquiry method with low self-efficacy, which resulted in low learning outcomes. However, there was no interaction between the inquiry method and self-efficacy.